2016
DOI: 10.1111/jnc.13716
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a fluorinated 4‐oxo‐quinoline derivative as a potential positron emission tomography radiotracer for imaging cannabinoid receptor type 2

Abstract: The cannabinoid receptor type 2 (CB2) is part of the endocannabinoid system and has gained growing attention in recent years because of its important role in neuroinflammatory/neurodegenerative diseases. Recently, we reported on a carbon-11 labeled 4-oxo-quinoline derivative, designated RS-016, as a promising radiotracer for imaging CB2 using PET. In this study, three novel fluorinated analogs of RS-016 were designed, synthesized, and pharmacologically evaluated. The results of our efforts led to the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…In 2015, Slavik et al reported a novel carbon-11 radiolabeled tracer 11 C- RS -016 for CB2R imaging, which showed higher specific binding in postmortem ALS patient spinal cord tissues [79,80]. Since then, several other recently synthetized radiotracers are under preclinical investigations and seem to offer promising prospects for imaging CB2R expression [115,116,117]. …”
Section: Potential Alternative Molecular Targets For Activated Micmentioning
confidence: 99%
“…In 2015, Slavik et al reported a novel carbon-11 radiolabeled tracer 11 C- RS -016 for CB2R imaging, which showed higher specific binding in postmortem ALS patient spinal cord tissues [79,80]. Since then, several other recently synthetized radiotracers are under preclinical investigations and seem to offer promising prospects for imaging CB2R expression [115,116,117]. …”
Section: Potential Alternative Molecular Targets For Activated Micmentioning
confidence: 99%
“…In addition to the 2‐oxoquinoline derivatives mentioned above, three 4‐oxoquinoline derivatives with different substitutions at the N‐1 position have been developed for the PET imaging of CB2 receptors (Figure 1C) . Similar to other radiotracers already mentioned, specific binding of these 4‐oxoquinoline radioligands to CB2 receptors was successfully demonstrated in in vitro autoradiography and in vivo PET scans again using CB2‐positive spleen .…”
Section: Cb2 Radioligands For Pet Imagingmentioning
confidence: 91%
“…In addition to the 2‐oxoquinoline derivatives mentioned above, three 4‐oxoquinoline derivatives with different substitutions at the N‐1 position have been developed for the PET imaging of CB2 receptors (Figure 1C) . Similar to other radiotracers already mentioned, specific binding of these 4‐oxoquinoline radioligands to CB2 receptors was successfully demonstrated in in vitro autoradiography and in vivo PET scans again using CB2‐positive spleen . Furthermore, the N‐1 pentyl derivative, [ 11 C]KD2, and the N ‐ethoxyethyl derivative, [ 11 C]RS‐016, showed specific binding in in vitro autoradiography performed on spinal cord slices derived from ALS patients, suggesting a potential use of CB2 radioligands in this specific neurodegenerative disease …”
Section: Cb2 Radioligands For Pet Imagingmentioning
confidence: 92%
See 1 more Smart Citation
“…The radioligand, 7 was chemically stable for up to 40 min, because no radioactive degradation or biotransformation products in human plasma after 40 min incubation time were detected (Supporting information). The shake‐flask method was applied to measure the distribution of [ 11 C]MPbP in n‐octanol/phosphate buffer pH 7.4 . The obtained logD 7.4 value 2.46±0.12 (n=5) suggests that the radioligand is sufficiently lipophilic for passive diffusion through the blood‐brain barrier (BBB).…”
Section: Figurementioning
confidence: 99%